A review of formwork systems for modern concrete construction. (April 2022) - Li, Wei; Lin, Xiaoshan; Bao, Ding Wen; Min Xie, Yi
Abstract: Concrete is a principal construction material in building industry. Formwork plays an important role in assisting geometry realisation and strength development of concrete elements. It is also one of the major costs in the construction of concrete structures. The use of formwork has a long history, and various formwork systems have been used in different projects. In the design and selection of formwork system, the requirements, such as safety, cost, structural geometry, construction time and surface quality need to be taken into account. This paper presents a comprehensive review of various formwork systems in concrete construction, including their raw materials, flexibility, fabrication methods, applications in concrete structures and environmental impacts. The advantages and current limitations of different formwork systems are compared and discussed, and finally recommendations are given.